Maize cob waste pre-treatments to enhance biogas production through co-anaerobic digestion with OFMSW. (February 2018) - Surra, Elena; Bernardo, Maria; Lapa, Nuno; Esteves, Isabel; Fonseca, Isabel; Mota, José Paulo
Graphical abstract: Highlights: H2 O2 pre-treatment increases MCW digestibility with low inhibitors formation. The use of MW in MCW pre-treatment with H2 O2 do not arise significant benefits. MCW pre-treated with H2 O2 with high reaction time causes some inhibition of AD. Co-AD of MCW with OFMSW allows significant enhancement of biogas and methane yields. Abstract: In the present work, the enhancement of biogas and methane yields through anaerobic co-digestion of the pre-hydrolised Organic Fraction of Municipal Solid Wastes (hOFMSW) and Maize Cob Wastes (MCW) in a lab-scale thermophilic anaerobic reactor was tested. In order to increase its biodegradability, MCW were submitted to an initial pre-treatment screening phase as follows: (i) microwave (MW) irradiation catalysed by NaOH, (ii) MW catalysed by glycerol in water and alkaline water solutions, (iii) MW catalysed by H2 O2 with pH of 9.8 and (iv) chemical pre-treatment at room temperature catalysed by H2 O2 with 4 h reaction time. The pre-treatments cataysed by H2 O2 were performed with 2% MCW (wMCW/v alkaline water) at ratios of 0.125, 0.25, 0.5 and 1.0 (wH2 O2 /wMCW). The pre-treatment that presented the most favourable balance between sugars, lignin, cellulose and hemicellulose solubilisations, as well as low production of phenolic compound and furfural (inhibitors), was the chemical pre-treatment catalysed by H2 O2, at room temperature, with a ratio of 0.5 wH2 O2 /wMCW (Pre1). This Pre1 was then optimised testing reaction times of 1, 2 and 3 days at a different pH (11.5) and MCW percentage (10% w/v). The optimised pre-treatment that presented the best results, considering the same criteria defined above, was the one carried out during 3 days, at pH 9.8 and 10% MCW w/v (Pre2). The anaerobic reactor was initially fed with the hOFMSW obtained from the hydrolysis tank of an industrial AD plant. The hOFMSW was than co-digested with MCW submitted to the pre-treatment Pre1. In another assay, hOFMSW was co-digested with MCW submitted pre-treatment Pre 2. The co-digestion of hOFMSW + Pre1 increased the biogas yield by 38.9% and methane yield by 29.7%, when compared to the results obtained with hOFMSW alone. The co-digestion of hOFMSW + Pre2 increased biogas yield by 46.0% and CH4 yield by 36.3%. In both cases, the methane content obtained in the biogas streams was above 66% v/v. These results show that pre-treatment with H2 O2, at room temperature, is a promising low cost way to valorize MCW through co-digestion with hOFMSW.